Review paperThe latest recommendations for the management of ankylosing spondylitis - Stanisławska-Biernat, Ewa (Reumatologia/Rheumatology, 2006)
Ankylosing spondylitis (AS) is a chronic inflammatory disease that leads to loss of function and disability in patients. AS is responsible for significant direct and indirect socioeconomic costs. Few studies have been performed on the treatment of patients with AS with disease-modifying antirheumatic drugs, none of which have proved clearly effective in axial disease. In the last few years the results of randomised controlled trials have raised good evidence that TNF-α blockade is very effective in AS and other spondyloarthropathies. Recently published guidelines for treatment of AS are discussed. There is a need for safety and socioeconomic data for long-term treatment with biologicals.